2021
DOI: 10.3390/su132212685
|View full text |Cite
|
Sign up to set email alerts
|

Explorative Study of Aquaponics Systems in Indonesia

Abstract: Aquaponics is the combined cultivation of fish in aquaculture systems and plants in hydroponic systems. This study aimed to explore and evaluate new aquaponics system designs in Jakarta, Indonesia, in terms of water and nutrient efficiency, and/or profitability. In total, one brackish water system with barramundi and tomato (BW) and three freshwater systems with Nile tilapia, rice, and duckweed (FW + DW), Nile tilapia and rice (FW − DW), and Nile tilapia and tomato (FW-tomato) were investigated using dynamic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The nal yield of rice and sh mainly depends on the coculture system, co-culture conditions, and aquatic animal species compositions. This nding was previously supported by several studies [17][18][19]21,26,67 . In India, Mohanty, et al 19 and T-R-NFT were 8.8, 5.8, 4.9, and 2.5 tonne ha − 1 , respectively, as compared to the traditional rice cultivation in Egypt, ranged from 6 to 8 tonne ha − 1 68 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The nal yield of rice and sh mainly depends on the coculture system, co-culture conditions, and aquatic animal species compositions. This nding was previously supported by several studies [17][18][19]21,26,67 . In India, Mohanty, et al 19 and T-R-NFT were 8.8, 5.8, 4.9, and 2.5 tonne ha − 1 , respectively, as compared to the traditional rice cultivation in Egypt, ranged from 6 to 8 tonne ha − 1 68 .…”
Section: Discussionsupporting
confidence: 79%
“…be attributed to the synergistic power of different feeding habits of aquatic animals in the IMTA system (mullet, cray sh, mussels, and silver carp), which signi cantly boosted the nutrient removal utilization e ciency. Tarigan, et al 21 investigated various rice-sh integrated aquaponics systems in freshwater and brackish water. The results of this study revealed increases in water use e ciency (31%), P (18%), and N (10%) in a freshwater treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of saved inorganic fertiliser can even substantially be increased depending on e.g. system type and design, fish stocking density, amount of feed, and daily water exchange rate, as has been shown already by other studies [14,[49][50][51]. Inorganic fertiliser production…”
Section: Plos Onementioning
confidence: 79%
“…Keunggulan lain dalam sistem hidroponik yaitu berbagai macam spesies tanaman dapat ditanam dalam sistem hidroponik. Sistem hidroponik ini dapat menghemat air dalam jumlah besar sehingga menghasilkan hasil panen yang lebih tinggi dan hampir tidak terpengaruh oleh perubahan iklim [4] . Pada sistem hidroponik, tanaman menerima semua nutrisi penting dari larutan kaya nutrisi.…”
Section: Latar Belakangunclassified